Pengaruh Langsung dan Tidak Langsung Dana Perimbangan Melalui Belanja Modal terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Evi Adriani; Ali Fahmi; Muhammad Syukri (Universitas Batanghari, 2021)
This study aims to find out: (1) The direct effect of balance funds on economic growth. (2) The indirect effect of balance funds through capital expenditures on economic growth. This study used secondary data in the form of panel data during the years 2014-2019 of districs/cities in Jambi Province. The data was obtained from the Central Statistics Agency (BPS) and the Directorate General of Financial Balance (DJPK). Path Analysis model with Linear Regression Analysis approach is gradually used to analyze the direct and indirect effect between exogenous and endogenous variables in the presence of intervening variables. The results showed that: (1) The balance fund directly had a significant effect on economic growth. (2) The balance funds indirectly through capital expenditures has no significant effect on economic growth. Based on the results, it was hope that provides benefits for local government to utilize effectively and efficiently the regional revenues and as input for further research to getting even better results.